2017
DOI: 10.1002/jmv.24795
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and clinical epidemiology of human respiratory syncytial virus (HRSV) A and B in hospitalized children, Southern Brazil

Abstract: Human respiratory syncytial virus (HRSV) is a major etiologic agent of pediatric respiratory infections. Genetic variability of its glycoprotein G enables HRSV to evade the immune response and determines its seasonal dissemination. This study reports genetic variability and clinical profiles of HRSV-infected patients from Southern Brazil. Seventy positive samples, 78% type A and 22% type B, were analyzed. Of the patients (median age, 6 months; interquartile range, 2-11 years), 16% had co-morbidities and 17% de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…Following the first reports of RSV-A ON1 in Canada [9] and Germany [14], genotype ON1 was detected in many other countries and regions [3, 13], including Asia [8, 1728], Africa [12, 2931], Europe [3239] and North and South America [4043]. In line with our results, several multi-season studies have previously reported ON1 to have rapidly replaced RSV-A non-ON1 genotypes [18, 19, 25, 28, 3033, 35, 3739, 4245]. Furthermore, ON1 has recently been reported to be the currently most prevalent RSV-A genotype worldwide [43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Following the first reports of RSV-A ON1 in Canada [9] and Germany [14], genotype ON1 was detected in many other countries and regions [3, 13], including Asia [8, 1728], Africa [12, 2931], Europe [3239] and North and South America [4043]. In line with our results, several multi-season studies have previously reported ON1 to have rapidly replaced RSV-A non-ON1 genotypes [18, 19, 25, 28, 3033, 35, 3739, 4245]. Furthermore, ON1 has recently been reported to be the currently most prevalent RSV-A genotype worldwide [43].…”
Section: Discussionsupporting
confidence: 90%
“…Some of previous inpatient studies comparing RSV-A ON1 with RSV-A non-ON1 genotypes found no difference in clinical severity [11, 38], while others showed divergent correlations between genotype ON1 and viral virulence [2]. Several authors have suggested a higher virulence of RSV-A ON1, based on the observation of higher rates of PICU admission and/or mechanical ventilation [42], earlier hospitalization and a higher rate of lower respiratory tract infections [19] or more frequent refusal to feed [44]. In contrast, three studies reported a milder course of illness associated with genotype ON1, such as a lower severity score [32], a lower rate of bronchopneumonia / lower respiratory tract disease [33, 35] and a lower hospitalization rate [33].…”
Section: Discussionmentioning
confidence: 99%
“…Yoshihara et al reported hospitalization incidence was significantly increased after the emergence of ON1, and risk of lower respiratory tract infection was 2.26 (95% CI: 1.37–3.72) times higher, and radiologically confirmed pneumonia was 1.98 (95% CI: 1.01–3.87) times greater in ON1 compared to NA1 [ 78 ]. A report from Brazil also noted an increase of intensive care unit admissions and need for mechanical ventilation associated with ON1genotype [ 79 ]. In contrast, reports from Italy, the Philippines, South Africa, Spain found no evidence of clinical differences in disease severity in correlation to genotype [ 30 , 56 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…While several authors have shown that the severity of the infection follows the viral load [4,5,37,38], others have not [7,12,33]. Some studies found an association between viral load and symptom frequency, but not severity itself [39,40]. Viral load measurement methods are widely variable between studies: some authors use plaque assay [4] or semi-quantitative analyses, such as ct [5,7,32], others use quantitative methods [38][39][40][41].…”
Section: Plos Onementioning
confidence: 99%